2010
DOI: 10.1063/1.3277055
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic clusters in the Brownmillerite bilayered compounds Ca2.5−xLaxSr0.5GaMn2O8: An approach to achieve layered spintronics materials

Abstract: We report the effect of La-substitution on the magnetic and magnetotransport properties of Brownmillerite-like bilayered compounds Ca 2.5-x La x Sr 0.5 GaMn 2 O 8 (x = 0, 0.05, 0.075, and 0.1) by using dc-magnetization, resistivity and magnetoresistance techniques. The Rietveld analysis of the room temperature x-ray diffraction patterns confirms no observable change of average crystal structure with the La-substitution. Both magnetic and magnetotransport properties are found to be very sensitive to the La-subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 67 publications
(97 reference statements)
4
20
1
Order By: Relevance
“…As a result, a ferromagnetic-like magnetic behaviour with enhanced magnetoresistance has been observed [17]. These properties make this type of naturally grown layered systems suitable for spintronics applications.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…As a result, a ferromagnetic-like magnetic behaviour with enhanced magnetoresistance has been observed [17]. These properties make this type of naturally grown layered systems suitable for spintronics applications.…”
Section: Introductionmentioning
confidence: 82%
“…Therefore, a decrease of T N is evident with the La substitution. Here, we would like to mention that our previous study using magnetization and magnetoresistance showed the appearance of FM interactions due to double exchange (DE) mechanism with electron doping or La substitution [17]. A competition between the leading superexchange (SE) AFM and the electron doping induced double exchange (DE) FM interactions may cause a decrease in the average SE AFM exchange interaction, resulting to the observed decrease of the T N value.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations